The Role of Teachers in Improving Student Discipline Development - Maswandi, Maswandi; Jumardi, Jumardi; Samsul, Samsul; Hasbullah, Hasbullah (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
The role of teachers is pivotal in shaping student discipline and fostering character development within the school environment. This study investigates the strategies employed by teachers at MTs Ar-Raihan Lattekko in enhancing the discipline of ninth-grade students. Utilizing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that teachers enact twelve key roles in discipline development, including acting as organizers, informants, class managers, demonstrators, mediators, facilitators, motivators, inspirators, initiators, evaluators, climatologists, and culminators. These roles are reflected through structured classroom management, daily behavioral guidance, provision of role models, motivation, and reward systems. Discipline techniques applied are rooted in democratic values, emphasizing preventive and supportive actions rather than punitive measures. This research highlights the effectiveness of teacher-led discipline strategies in shaping responsible student behavior, offering valuable insights for educational institutions seeking to strengthen character education.